Полупроводниковый генератор импульсного действия с электронным переключением частот Ka-диапазона - Dvornichenko, V. P.; Karushkin, N. F.; Malyshko, V. V.; Orekhovskii, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2015)
Transmitting devices for small radars in the millimetre wavelength range with high resolution on range and noise immunity. The work presents the results of research and development of compact pulse oscillators with digital frequency switching from pulse to pulse. The oscillator consists of a frequency synthesizer and a synchronized amplifier on the IMPATT diode. The reference oscillator of the synthesizer is synchronized by a crystal oscillator with digital PLL system and contains a frequency multiplier and an amplifier operating in pulse mode. A small-sized frequency synthesizer of 8 mm wave lengths provides an output power of 1.2 W per pulse with a frequency stability of no worse than 2.10–6. Radiation frequency is controlled by a three-digit binary code in OOL levels. Synchronized amplifier made on IMPATT diodes provides microwave power up to 20 W in oscillator output with microwave pulse duration of 100 – 300 ns in an operating band. The oscillator can be used as a driving source for the synchronization of semiconductor and electro-vacuum devices of pulsed mode, and also as a transmitting device for small-sized radar of millimeter wave range.